2017
DOI: 10.12657/folmal.025.024
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of field bean cultivars to slug damage

Abstract: In recent years field bean crops (Vicia faba) have been frequently attacked by slugs. As there are no molluscicides registered for protection of field beans against slugs, alternative anti-slug measures are needed. One of them may be using specific cultivar properties of the plant. The aim of the study was to assess the susceptibility of different field bean cultivars to damage by slugs and to identify the effect of tannin content in plants on the extent of damage. The experiments were performed in the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In one of the studies, the authors found 3,5-dimethoxycinnamic acid inefficient, unlike cinnamic amide. Furthermore, plants can produce repellents for the protection against slugs (Linhart & Thompson, 1995;Dodds et al, 1996;Clark et al, 1997;Wood & Ligare, 2008;Shannon et al, 2016;Jaskulska et al, 2017). Jeong et al (2012) conducted laboratory studies with natural products, such as nicotine extract and caffeine, or their mix with ethyl alcohol as molluscicides.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the studies, the authors found 3,5-dimethoxycinnamic acid inefficient, unlike cinnamic amide. Furthermore, plants can produce repellents for the protection against slugs (Linhart & Thompson, 1995;Dodds et al, 1996;Clark et al, 1997;Wood & Ligare, 2008;Shannon et al, 2016;Jaskulska et al, 2017). Jeong et al (2012) conducted laboratory studies with natural products, such as nicotine extract and caffeine, or their mix with ethyl alcohol as molluscicides.…”
Section: Introductionmentioning
confidence: 99%
“…Pestiferous slugs cause damage to a diverse range of agricultural and horticultural crops throughout the world (Askary, 2010;Askary et al, 2017, Cordoba et al, 2018Fritz et al, 2001;South, 2012;Speiser et al, 2001) primarily by feeding directly on the plant (Ester and Trul, 2000;Frank, 1998;Gould, 1961;Jaskulska et al, 2017) and/or as vectors of plant pathogens (Hasan and Vago, 1966). This results in significant economic losses to growers (Willis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%